Pengaruh Kompetensi dan Independensi pada Kinerja Auditor Internal Pemerintah dengan Etika Auditor sebagai Variabel Moderasi (Studi Pada Inspektorat Kabupaten Tegal) - Uly Maria Ulfah; Fitri Lukiastuti (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2018)
Government internal auditors must comply with labor regulations as civil servants and must comply with the APIP code of ethics and APIP audit standards that have been established when conducting guidance and supervision. Auditors need two main things, namely competence and independence to produce high audit quality. This study aims to provide empirical evidence about the influence of competence and independence on the performance of government internal auditors, as well as the role of auditor ethics in moderating the influence of competence and independence on the performance of government internal auditors. The population in this study are all auditors who work in the Tegal District Inspectorate, amounting to 40 people. The analytical method used is Moderated Regression Analysis. The results of the study prove that auditor competence and independence have a positive and significant effect on auditor performance. Other results from auditor ethics analyze the relationship between competency and auditor independence to auditor performance.